Hubungan Kualitas Layanan dengan Status Gizi Ibu Hamil di Wilayah Kerja Puskesmas Tanasitolo Wajo - Sandi, Eka Oktavia; Hamdiyah, Hamdiyah; Kenre, Ishak; Syahriani, Syahriani; Sukarta, Asmah (Jurnal Kebidanan Malakbi, 2023)
The high mortality rate of pregnant women requires pregnant women to perform antenatal care (ANC) examinations. The nutritional quality of women during pregnancy is still a problem in developing countries. The incidence of anemia in pregnant women in Wajo district in 2019 increased to 7,096 people (27.42%). Therefore, it is necessary to conduct a survey to detect the interaction between the quality of ANC services and the nutritional condition of pregnant women. The purpose of this study was to determine the relationship between the quality of antenatal care and the nutritional status of pregnant women in the working area of ​​the Tanasitolo Public Health Center, Wajo Regency in 2022. This study was conducted with a cross-sectional research design, the survey was held at the Tanasitolo Health Center, Wajo Regency in July 2022. The population is 35 pregnant women in the III trimester. Sampling technique by applying the total sampling technique. The results showed that the P value had no significant relationship between the quality of antenatal care services and the P value of LILA (0.296 > 0.05), BMI (0.283 > 0.05), Hemoglobin Level (0.703 > 0.05). The conclusion of this study is that there is no relationship between the nutritional status of pregnant women and antenatal care services in the work area of the Tanasitolo Health Center, Wajo Regency in 2022. It is recommended to pay more attention to the quality of examinations for pregnant women and further improve services and facilities for mothers during pregnancy, especially in health service examinations so that risks and complications in the process of pregnancy, childbirth and post partum can be detected earlier so that prevention can be carried out as early as possible